Defoe's footprints : essays in honour of Maximillian E. Novak - Maniquis, Robert M.; Fisher, Carl, 1958-; Novak, Maximillian E. (Published by the University of Toronto Press in association with the UCLA Center for Seventeenth- and Eighteenth-Century Studies and the William Andrews Clark Memorial Library, 2009)
With attention to Defoe's neglected writings as well as to his important works, this volume uncovers his distance from and influence on modern literature, paying tribute to Maximillian E. Novak by presenting new ideas about, and new readings of, Daniel Defoe.
"Maximilian E. Novak: a bibliography" (p. [239]-249).
Keywords: Defoe, Daniel, -- 1661?-1731 -- Criticism and interpretation.; Defoe, Daniel, -- 1661?-1731; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Literary criticism; Festschriften; Criticism, interpretation, etc.; Festschriften.; Literary criticism.; Critiques littéraires.